Local processes and Global History in the examination of the Lower Guadiana Bassin's borderlands (Portugal and Spain) (Tempo e Argumento, 2022)
In this paper we examine the use of recent methodologies from Global Studies in the study of borderlands. Borders or boundaries are critical for the development of unique social relations and interconnections. This study is mostly focused on the Lower Guadiana Valley, which separates partially two countries (Portugal and Spain). Permeability and the development of local processes in time and space are also examined, which leads to the assumption that borderlands are idoneous case-studies for Global History.Keywords: history; border studies; archaeology; cultural heritage.